Injectable glycol chitosan thermogel formulation for efficient inner ear drug delivery. (15th February 2022) - Yu, Yang; Kim, Da Hae; Suh, Eun Yeong; Jeong, Seong-Hun; Kwon, Hyuk Chan; Le, Thi Phuc; Kim, Yugyeong; Shin, Sun-Ae; Park, Yong-Ho; Huh, Kang Moo
Abstract: We prepared a new injectable thermogel to enhance the efficiency of inner ear delivery of dexamethasone (DEX). Hexanoyl glycol chitosan (HGC) was synthesized and evaluated as an amphiphilic thermogel (Tgel  ~ 32 °C) for use as a solubilizing agent as well as an injectable carrier for intratympanic delivery of the hydrophilic and hydrophobic forms of DEX. Various thermogel formulations with different drug types and concentrations were prepared, and their physicochemical and thermogelling properties were characterized by 1 H NMR, ATR-FTIR, and rheometer. They exhibited versatile release kinetics from several hours to more than 2 weeks, depending on drug type and concentration. Our formulations further showed good residual stability for more than 21 days without any cytotoxicity or inflammation in the middle and inner ear and could deliver a considerably high drug concentration into the inner ear. Therefore, HGC thermogel has great potential as an effective and safe formulation for inner ear drug delivery. Graphical abstract: Unlabelled Image Highlights: Hexanoyl glycol chitosan (HGC) was designed as an injectable thermogel for inner ear drug delivery. HGC thermogels exhibited versatile release kinetics with no initial burst. HGC thermogels showed good residual stability without side effects in the middle ear cavity. HGC formulations could deliver a considerably high drug concentration into the inner ear.